Power relations and art education: body/memory as a subversive force in postmodernity (Revista Apotheke, 2022)
The power regimes imbricated in the profusion of images in the contemporary scenario end up requiring a more active posture on the part of art educators in the sense of reclaiming their sayings and tensioning their discourses. Therefore, memory and the body emerge as opportune instances to erase the essentialisms inherited from modernity, highlighting other ways of re-signifying the transit of meanings from the many rationalities that coexist in the symbolic field. Thus, I propose an epistemological analysis of power-knowledge, body and memory, aiming to contribute to problematizations around the role of art education in post-modern society.